Physicochemical properties of β-carotene and eugenol co-encapsulated flax seed oil powders using OSA starches as wall material. (December 2017) - Sharif, Hafiz Rizwan; Goff, H. Douglas; Majeed, Hamid; Shamoon, Muhammad; Liu, Fei; Nsor-Atindana, John; Haider, Junaid; Liang, Rong; Zhong, Fang
Abstract: Food industry is concentrating on development of novel functional foods fortified/enriched with lipophilic bioactives to improve health and well-being of consumers. β-carotene (BC) and eugenol (EU) co-encapsulated flax seed oil (FSO) emulsions stabilized by octenyl succinic anhydride modified starches (OSA-MS) were spray dried to powders after the emulsification process. Microcapsules showed good dissolution behavior, high (≈90%) microencapsulation efficiency and semi-spherical morphology observed by scanning electron microscopy. A 28 days storage test at 40 °C was carried out to evaluate the effect on physicochemical properties of microcapsules. Microcapsules encapsulated by lower Mw OSA-MS-1 presented higher oxidative stability, lower moisture contents and water activity during storage compared to high Mw OSA-MS-2. Incorporation of EU played its antioxidant role and further improved the oxidative stability as well as retention of core materials. Microcapsules of OSA-MS-1 containing FSO + BC + EU exhibited the maximum retention of BC (71%), EU (84%) and α-linolenic acid (92%). This study indicated a positive role of EU as antioxidant and low Mw OSA-starch as wall material for the encapsulation of lipophilic bioactives that could be used for the development of functional foods and beverages. Graphical abstract: Highlights: FSO, BC and EU were co-encapsulated using two different OSA-MS as wall material. Microcapsules of OSA-MS-1 showed better physicochemical properties during storage. Incorporation of EU improved the oxidative stability. Maximum retention of BC (71%), EU (84%) and ALA (92%) were obtained during storage. OSA-MS-1 was found better over OSA-MS-2 due to its lower Mw and density.